2015
DOI: 10.5194/acp-15-12445-2015
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol size distribution and new particle formation in the western Yangtze River Delta of China: 2 years of measurements at the SORPES station

Abstract: Abstract. Aerosol particles play important roles in regional air quality and global climate change. In this study, we analyzed 2 years (2011)(2012)(2013) of measurements of submicron particles (6-800 nm) at a suburban site in the western Yangtze River Delta (YRD) of eastern China. The number concentrations (NCs) of particles in the nucleation, Aitken and accumulation modes were 5300 ± 5500, 8000 ± 4400, 5800 ± 3200 cm −3 , respectively. The NCs of total particles are comparable to those at urban/suburban sites… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
107
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 76 publications
(100 reference statements)
11
107
1
Order By: Relevance
“…In addition to gaseous precursors participating in nucleation and subsequent condensational growth, there has been a consensus that the occurrence of a NPF event is also limited by A Fuchs , because the survival possibility of nucleated particles is suppressed when the coagulation scavenging effect is significant (Weber et al, 1997;Kerminen et al, 2001;Kuang et al, 2012). Reported average A Fuchs (or in the form of a condensation sink) on NPF days was found to be lower than that on non-event days at several locations (Dal Maso et al, 2005;Gong et al, 2010;Qi et al, 2015).…”
Section: R Cai Et Al: Aerosol Surface Area Concentrationmentioning
confidence: 99%
“…In addition to gaseous precursors participating in nucleation and subsequent condensational growth, there has been a consensus that the occurrence of a NPF event is also limited by A Fuchs , because the survival possibility of nucleated particles is suppressed when the coagulation scavenging effect is significant (Weber et al, 1997;Kerminen et al, 2001;Kuang et al, 2012). Reported average A Fuchs (or in the form of a condensation sink) on NPF days was found to be lower than that on non-event days at several locations (Dal Maso et al, 2005;Gong et al, 2010;Qi et al, 2015).…”
Section: R Cai Et Al: Aerosol Surface Area Concentrationmentioning
confidence: 99%
“…In most previous studies, the above population balance method was used to estimate new particle formation rates in China. The reported formation rates of 3 nm particles and larger ones are typically in the range of 1-10 cm −3 s −1 (Wang et al, 2013;Leng et al, 2014;An et al, 2015;Qi et al, 2015). One study in Shanghai reported a rate of 112.4 to 271.0 cm −3 s −1 for the formation of 1.5 nm particles inferred from a DEG-CPC (Xiao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most economically invigorating and densely populated countries, China features simultaneous high aerosol loadings and NPF rates (S. Gao et al, 2011;Guo et al, 2012;Qi et al, 2015). Moreover, the condensational growth of nucleation-mode particles has been indicated as a plausible cause of regional haze events (Guo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%